Similarities and Differences Between Gerontal and Young Patients with Acute Pancreatitis: Evaluation of Clinical Characteristics and Outcomes - Asfuroğlu Kalkan, Emra; Kalkan, Çağdaş; Kaçar, Sabite; Barutçu, Sezgin; Yüksel, Mahmut; Güçbey Türker, Özge; Göre, Burak; Canlı, Tolga; Asfuroğlu, Umut; Barutçu Asfuroğlu, Berrak; et al. (Turkish Journal of Gastroenterology, 2022)
Background: Acute pancreatitis is an abrupt inflammatory disease of the exocrine pancreas and it can occur in different severities. It is becoming more common and more mortal in the gerontal population. The aim of our study was to explore the similarities and differences between young and gerontal patients with acute pancreatitis, with a special emphasis on patients over 80 years of age. Methods: Medical records of patients (n = 1150) with acute pancreatitis were analyzed retrospectively. Several scoring systems including Bedside index for severity in acute pancreatitis, Ranson’s score, Harmless acute pancreatitis score, Acute Physiology and Chronic Health Evaluation, Balthazar Grade, Glasgow score, and Japanese severity score were applied at admission. Patients were divided into 3 groups; group I, young group (n = 706), if they were aged <65 years; group II, older group (n = 338), if they were aged ≥65 years to <80 years; group III, octogenarian group (n = 106), if they were aged ≥ 0 years. Results: In total, 1150 patients with acute pancreatitis were analyzed. Octogenarian group (n = 42, 39.6%) showed a more severe acute pancreatitis compared to patients in group I (n = 15, 2.1%) and II (n = 50, 14.8%, P < .001). Complications were more common in patients in group III (P < .001). Mortality rate was higher in patients in group III (n = 53, 50%) compared to group I (n = 8, 1.1%) and group II (n = 53, 15.7%) (P < .001). Conclusion: Gerontal patients with acute pancreatitis tend to have more severe disease and systemic and local complications. Mortality rates were higher in older patients compared to younger patients. Cite this article as: Asfuroğlu Kalkan E, Kalkan Ç, Kaçar S, et al. Similarities and differences between gerontal and young patients with acute pancreatitis: Evaluation of clinical characteristics and outcomes. Turk J Gastroenterol. 2022;33(10):874-884.